PERAN DINAS PERHUBUNGAN KABUPATEN BOJONEGORO DALAM MENINGKATKAN PELAYANAN ANGKUTAN KOTA - Ari Kuntardina; Muhammad Handono (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2014)
Public transport route in the city is an important means of transportation for people of Bojonegoro. The existence and the services provided public transport affects the level of satisfaction of public service users of the freight. Besides, the role of the Department of Transportation also affects the trajectory of public transport services in the city. This research is a qualitative descriptive study aims to determine the role of the Department of Transportation in the improvement of public transport service route in the city. The population is people who use public transport route in the city, and the sample amounted to 50 people. While the methods and techniques of data collection using questionnaires and interview. Data Analysis Techniques used is a model of Miles and Hubberman, with the result that people who are not satisfied with the service of urban transportation route in the city due to the condition of urban transportation that are less good, less comfortable, time spent waiting for shuttles were long, the behavior of the driver reckless in driving, as well as inadequate halte. And the role of the Department of Transportation Bojonegoro deemed not optimal in achieving safe transportation.